Do social media enhance constructive employee voice all of the time or just some of the time?. (14th July 2015) - Martin, Graeme; Parry, Emma; Flowers, Paul
Abstract : Social media are becoming widely adopted by organisations to encourage collaboration and communication. We seek to understand how social media can enhance employee voice and employees' willingness to engage in constructive dialogue with both colleagues and managers. By drawing on literature on employee voice, signalling theory and personal control to analyse qualitative data from research into three strategic business units in a major global telecommunications corporation, we find that (a) employee perceptions of personal control and autonomy influence whether and how employees' exercise voice through social media, and (b) these perceptions vary according to different organisational/field‐level contexts evident in the corporation.